Use of micronucleus cytome assays with buccal cells for the detection of genotoxic effects: A systematic review and meta-analysis of occupational exposures to metals - Wultsch, Georg; Nersesyan, Armen; Kundi, Michael; Fenech, Michael; Eibensteiner, Florian; Mišík, Miroslav; Krupitza, Georg; Ferk, Franziska; Knasmüller, Siegfried (Mutation research. Reviews in mutation research, 2024)
Micronucleus (MN) assays with buccal cells are at present widely used to investigate occupational exposures to genotoxic carcinogens. This article describes their use for the monitoring of metal exposed workers. We found in total 73 relevant articles, in the majority (97 %) increased MN and/or other nuclear anomalies were reported. Most studies were realized in South East Asia and South America. A variety of different occupations was studied including welders, electroplaters, painters, workers in battery recycling and production, tannery workers, dental technicians, miners, workers in foundries and smelters, and also subjects working in waste recycling, glass, aluminum and steel production. In many investigations the effects increased with the duration of the working period. The quality of individual studies was evaluated with a quality score tool. The number of cells was in most studies sufficient and DNA-specific stains were used. However, many studies have shortcomings, e.g. they focused solely on MN formation and did not evaluate anomalies, which provide additional information about the stability of the genetic material and acute cytotoxic effects. Only 35 % of the investigations contain quantitative information about exposures to metals and other toxicants. In 6 of these studies, correlations were observed between the concentrations of specific metals (As, Pb, Cr, Cd) in body fluids and MN frequencies. Taken together, the available data indicate that the MN assay can be used to detect chromosomal damage in metal exposed groups; furthermore, it enables also comparisons between subgroups differing in regard to their exposure and allows an estimation of the efficiency of protective measures. The exposure of workers to metals is currently controlled with chemical analytical measurements only, MN assays with buccal cells could contribute to further improve the safety at workplaces as they reflect the biological consequences including synergistic and antagonistic interactions between toxicants.